The Agent-Agents Problem: Payment by Relative Output - Carmichael, H. Lorne (Journal of Labor Economics, 1983)
This paper begins an investigation into the incentive problems at a firm when the effort of the employer and the employees combines to determine final output. The major conclusion is that optimal reward functions in this circumstance will in general value the performance of a worker relative to that of his peers. The paper thus joins a growing literature associated with the work of Lazear and Rosen on rank-order tournaments.